1980
DOI: 10.1056/nejm198012253032601
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Autoantibodies to Beta Cells in the Serum of Patients with Insulin-Dependent Diabetes Mellitus

Abstract: We studied serum from 36 patients with insulin-dependent diabetes mellitus (IDDM) for the capacity to lyse beta cells. Immunofluorescence revealed an islet-cell cytoplasmic antibody (ICA) in 20 patients with IDDM and an islet-cell-surface antibody (ICSA) in 23. Neither ICA nor ICSA was found in any of 21 normal controls or 15 patients with non-insulin-dependent diabetes. In the presence of complement. ICSA-positive serum caused significant lysis as measured by release of 51Cr (50.1 +/- 8.8 per cent) from cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
93
1
3

Year Published

1981
1981
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(102 citation statements)
references
References 30 publications
5
93
1
3
Order By: Relevance
“…However, the IDDM patients used in the latter study had been diagnosed some years earlier (mean 3 years, range 2-23 years), thus it is probable that reduced circulating autoantibody and activated complement components in these patients may explain the low levels reported (Bergamaschini et al 1991) compared with those reported here for newly diagnosed patients. Other reports have shown that complement-fixing islet cell antibodies are increased in the serum of IDDM individuals (Bonifacio et al 1995, Dobersen et al 1980. The previous studies may have been unable to detect significant levels of activated complement in serum from IDDM patients, because of lack of availablity or poor specificity of antibodies used for the TCC ELISA.…”
Section: Discussionmentioning
confidence: 92%
“…However, the IDDM patients used in the latter study had been diagnosed some years earlier (mean 3 years, range 2-23 years), thus it is probable that reduced circulating autoantibody and activated complement components in these patients may explain the low levels reported (Bergamaschini et al 1991) compared with those reported here for newly diagnosed patients. Other reports have shown that complement-fixing islet cell antibodies are increased in the serum of IDDM individuals (Bonifacio et al 1995, Dobersen et al 1980. The previous studies may have been unable to detect significant levels of activated complement in serum from IDDM patients, because of lack of availablity or poor specificity of antibodies used for the TCC ELISA.…”
Section: Discussionmentioning
confidence: 92%
“…The presence of islet cell surface antibodies capable of mediating a complement-dependent cytotoxic reaction does not necessarily imply that these antibodies are actively 'diabetogenic' since they have been found in a large proportion of first degree relatives of diabetic probands [18]. The various approaches to islet cell antibody determination and the different characters of the tissue preparations may be taken as an argument that islet cell antibodies are directed against several different antigens.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Most reports are of indirect observations, but recent studies have attempted to associate immune mechanisms to human diabetes using complement-dependent antibody-mediated cytotoxicity (C'AMC) assays [3][4][5][6][7]. Cytotoxicity assays in vitro and the reported results vary, but each method described uses islet derived target cells.…”
mentioning
confidence: 99%
“…Cytotoxicity assays in vitro and the reported results vary, but each method described uses islet derived target cells. One report suggests that virtually all sera from Type 1 diabetic patients have C'AMC against cultured rat islet cells, and that sera from non-diabetic parents and siblings also mediated C'AMC [6]. Using intact normal rodent islets or rat or human islet turnout target cells, 10%-30% of patients' sera have C'AMC [3][4][5]7].…”
mentioning
confidence: 99%